An unsupervised method for dominant colour region segmentation in yarn‐dyed fabrics. (7th October 2013) - Luo, Lin; Shao, Si‐Jie; Shen, Hui‐Liang; Xin, John H
<x xml:space="preserve">Abstract</x> This paper presents a novel unsupervised approach to detect dominant colour regions standing out conspicuously in yarn‐dyed fabric images. For a dominant colour region of a yarn‐dyed fabric, measured by an imaging system, its individual yarn has an irregular three‐dimensional shape resulting in significant colour difference among pixels of the yarn. This difference leads to difficulty in segmenting yarns into dominant colour regions. A probabilistic model is proposed in this study to associate the colour of a dominant colour region with the colours of its yarns. Based on this model, the colour histograms of a dominant colour region are first estimated from those of yarns in a yarn‐dyed fabric image. Then, a hierarchical segmentation structure is devised to detect dominant colour regions in the image. Experimental results show that the proposed approach achieves satisfactory performance for dominant colour region segmentation in yarn‐dyed fabric images, with high computational efficiency.